Paradigms of Canonization: Best Seller vs Classics? A Look at the Extreme Contemporary (Altre Modernità, 2025)
What happens to best sellers? And how are they related to canonization paths? In an attempt to provide exhaustive answers to these questions, the article proposes a historical excursus through bourgeois Modernity until reaching the Extreme Contemporary. The long course of literary history shows how value paradigms change as readers change, as historical epochs change, and as production systems change. The study therefore intends to set the necessary historical and methodological preconditions for reading the changes taking place in the production of contemporary best sellers and to grasp the possible repercussions on the paths of canonization of what we read and ‘watch‘ today.
Keywords: classical works; value paradigms; Literary Modernity; Extreme Contemporary